Challenges experienced in the practice of sign bilingual education as a strategy for inclusion of deaf children in mainstream schools in Zimbabwe - Sibanda, Patrick; Tlale, Lloyd Daniel Nkoli (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study sought to establish and examine challenges that could be experienced in the practice of sign bilingual education as a strategy for inclusion of deaf children in mainstream schools in Zimbabwe. The study was predominantly qualitative and adopted both discourse and conversation analysis designs. Personal face-to-face and focus group interviews were used to collect data which were presented in form of direct quotations and descriptive summaries and analysed using theme identification and thick descriptions. The study revealed that the challenges experienced in the practice of sign bilingual education as a strategy for inclusion of deaf children in Zimbabwe included denial, negative and non-committal attitudes; limited or lack of resources and skills; unclear policies and low enrolment of deaf children in mainstream schools. On these bases, the study concluded that, if not mitigated, these challenges could make it difficult for the country to realise the full benefits of sign bilingual education as a strategy for the inclusion of deaf children in mainstream schools in the country. In response, the study recommended awareness campaigns, training and staff development, resource mobilisation, policy review, early exposure and coenrolment as means of mitigating these challenges.